Mutations underlying 3-Hydroxy-3-Methylglutaryl CoA Lyase deficiency in the Saudi population - Rashed Mohammed S; Alsmadi Osama A; Imtiaz Faiqa; Al-Sayed Moeenaldeen; Meyer Brian F (BMC, 2006)
Abstract Background 3-Hydroxy-3-Methylglutaric aciduria (3HMG, McKusick: 246450) is an autosomal recessive branched chain organic aciduria caused by deficiency of the enzyme 3-Hydroxy-3-Methylglutaryl CoA lyase (HL, HMGCL, EC 4.1.3.4). HL is encoded by HMGCL gene and many mutations have been reported. 3HMG is commonly observed in Saudi Arabia. Methods We utilized Whole Genome Amplification (WGA), PCR and direct sequencing to identify mutations underlying 3HMG in the Saudi population. Two patients from two unrelated families and thirty-four 3HMG positive dried blood spots (DBS) were included. Results We detected the common missense mutation R41Q in 89% of the tested alleles (64 alleles). 2 alleles carried the frame shift mutation F305fs (-2) and the last two alleles had a novel splice site donor IVS6+1G>A mutation which was confirmed by its absence in more than 100 chromosomes from the normal population. All mutations were present in a homozygous state, reflecting extensive consanguinity. The high frequency of R41Q is consistent with a founder effect. Together the three mutations described account for >94% of the pathogenic mutations underlying 3HMG in Saudi Arabia. Conclusion Our study provides the most extensive genotype analysis on 3HMG patients from Saudi Arabia. Our findings have direct implications on rapid molecular diagnosis, prenatal and pre-implantation diagnosis and population based prevention programs directed towards 3HMG.